Developing skills for employability with German partners : 8 case studies of train-the-trainer solutions - (:unkn) unknown (iMOVE, 2019)
"This brochure highlights eight success stories of train-the-trainer solutions, realized in a joint effort by German and international partners. With its wide range of training programmes and its strong emphasis on employability, 'Training – Made in Germany' has the potential to successfully contribute to the design process of training systems in many countries through transnational cooperation projects." (Excerpt, BIBB-Doku)
Keywords: Berufsbildung; Internationale Zusammenarbeit; Bildungsexport; E-Learning; digitale Medien